2012
DOI: 10.1152/ajpheart.00395.2012
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca2+ binding of cardiac troponin reduces sarcomere length dependence of contractile activation independently of strong crossbridges

Abstract: Calcium sensitivity of the force-pCa relationship depends strongly on sarcomere length (SL) in cardiac muscle and is considered to be the cellular basis of the Frank-Starling law of the heart. SL dependence may involve changes in myofilament lattice spacing and/or myosin crossbridge orientation to increase probability of binding to actin at longer SLs. We used the L48Q cardiac troponin C (cTnC) variant, which has enhanced Ca(2+) binding affinity, to test the hypotheses that the intrinsic properties of cTnC are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…This hypothesis was based on previous results, where L48Q cTnC enhanced the Ca 2+ binding properties of cTn and thin filaments in solution, and the Ca 2+ sensitivity of myofilament contraction [23,24]. In this study we found that an ~20% myofilament incorporation of L48Q cTnC increased contractility of cardiomyocytes from both healthy hearts and hearts with systolic dysfunction (post-MI).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This hypothesis was based on previous results, where L48Q cTnC enhanced the Ca 2+ binding properties of cTn and thin filaments in solution, and the Ca 2+ sensitivity of myofilament contraction [23,24]. In this study we found that an ~20% myofilament incorporation of L48Q cTnC increased contractility of cardiomyocytes from both healthy hearts and hearts with systolic dysfunction (post-MI).…”
Section: Discussionsupporting
confidence: 77%
“…Recent work by our group [21,23,24] suggests that the mechanism of by which L48Q cTnC increases contraction of intact cardiomyocytes is by augmented Ca 2+ binding to cTn that results in increased thin filament activation at any given [Ca 2+ ]. Our solution studies, and work by others [22], have demonstrated that the L48Q point mutation significantly increases the Ca 2+ affinity of cTnC and increases the affinity of cTnC for cTnI in both the presence and absence of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations